2005
DOI: 10.1080/02652030400027995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contaminant and residue levels in organic and conventional milk and meat products from Northern Italy

Abstract: Due to the growing interest in organic products, a comparison between the chemical safety of organic and conventional products was undertaken. Milk and meat were the products chosen for study. The parameters evaluated to assess chemical safety were organochlorine pesticides, polychlorinated biphenyls (PCBs), lead, cadmium and mycotoxin contamination. Pesticides and PCBs residues in both organic and conventional milk and meat were lower than legal limits. Lead and cadmium residues were very low and did not diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 10 publications
2
35
0
2
Order By: Relevance
“…The same behavior is observed in previous studies on lead, cadmium and aflatoxins in the infant cereals (Hernández-Martínez, & Navarro-Blasco, 2012;. On the contrary, other reported studies suggest little difference in the arsenic content found in organic vegetables with respect to their ordinary or conventional production (Ghidini et al, 2005); only selective, occasional and sporadic contaminations may explain high levels of these contaminants (Malmauret, Parent-Massin, Hardy, & Verger, 2002).…”
Section: Influence Of Cereal Production Methods On Mercury and Arsenicmentioning
confidence: 37%
“…The same behavior is observed in previous studies on lead, cadmium and aflatoxins in the infant cereals (Hernández-Martínez, & Navarro-Blasco, 2012;. On the contrary, other reported studies suggest little difference in the arsenic content found in organic vegetables with respect to their ordinary or conventional production (Ghidini et al, 2005); only selective, occasional and sporadic contaminations may explain high levels of these contaminants (Malmauret, Parent-Massin, Hardy, & Verger, 2002).…”
Section: Influence Of Cereal Production Methods On Mercury and Arsenicmentioning
confidence: 37%
“…Certain studies have scientifically proven the benefits of organic products regarding lower content in synthetic agrochemicals (Poulsen & Andersen, 2003;Andersen, & Poulsen, 2001), nitrate and nitrite (De Martin & Restani, 2003), and drug residues (Cabaret, Mage, & Bouilhol, 2002;Carstensen, Vaarts, & Roepstorff, 2002), however a lack of differentiation in metal elements has also been demonstrated (Magkos, Arvaniti, & Zampelas, 2006). Thus, the organically produced vegetables exhibited no significant differences in relation to the levels of heavy metals from conventional production (Ghidini et al, 2005;Woese, Lange, Boess, & Werner-Bögl, 1997). Nevertheless, other authors showed marked differences against organic production.…”
Section: Influence Of Cereal Production Methods On Lead and Cadmium Comentioning
confidence: 79%
“…No marked differences in OTA levels were found in cereal derivatives in Italy (Biffi et al, 2004) or in cereal-based baby food (Beretta et al, 2002). Two studies have observed lower levels of aflatoxin in organic milks compared with conventional ones (Gravert et al, 1989;Frank Hansen, 1990), whereas another one found some high levels in organic milk (Ghidini et al, 2005). Organic beers collected in Belgium during [2003][2004] were more frequently OTA-contaminated than their conventional counterparts but this difference was not found in 2005 (Anselme et al, 2006).…”
Section: Mycotoxinsmentioning
confidence: 99%